Prominent Hypercoagulability Associated With Inflammatory State Among Cancer Patients With SARS-CoV-2 Infection - Xiong, Bei; Liu, Tao; Luo, Ping; Wei, Yongchang; Zhou, Yi; Liu, Minghui; Zhang, Yongxi; Wang, Hanlun; Zhang, Xiaochun; Wang, Xinghuan; Zhou, Fuling (Frontiers in Oncology, 2020)
Abnormal coagulation parameters and potential benefits of anticoagulant therapy in general population with novel coronavirus pneumonia (COVID-19) have been reported. However, limited data are available on cancer patients. Coagulation indexes and inflammation parameters in 57 cancer patients with SARS-CoV-2 infection with different severity were retrospectively analyzed. We found that D-dimer levels were increased in 33 patients (57.9%, median: 790 ng/mL). Compared with ordinary type patients, severe and critical ill patients had decreased MPV values (P =0.006), prolonged PT (median: 13.3 vs 11.5 vs 11.4s, P ＜0.001), significant higher D-dimer levels (median: 2400 vs 940 vs 280 ng/mL, P ＜0.001), higher PCT levels (median:0.17 vs 0.055 vs 0.045 ng/mL, P =0.002), higher IL-6 (median:20.6 vs 2.3 vs 3.0 pg/mL, P =0.040) and decreased PaO2 (median:68 vs 84 vs 96 mm Hg, P ＜0.001). Importantly, three patients, one severe and two critical ill type, with increased D-dimer survived after anticoagulant therapy with continuous heparin infusion. Increased D-dimer levels positively correlated with increased PCT levels (r = 0.456, P = 0.002) and IL-6 levels (r = 0.501, P = 0.045). A negative correlation between D-dimer levels and PaO2 levels (r = -0.654, P = 0.021) were also existed. Cancer patients with COVID-19 showed prominent hypercoagulability associated with severe inflammation, anticoagulation therapy might be useful to improve the prognosis and should be immediately used after the onset of hypercoagulability.